Validation of an Individualized Measure of Quality of Life, Patient Generated Index, for Use with People with Parkinson’s Disease - Ayse Kuspinar; Kedar K. V. Mate; Anne-Louise Lafontaine; Nancy Mayo (Neurology Research International)
Introduction. Parkinson’s disease (PD) affects all aspects of an individual’s life and is heterogeneous across people and time. The Patient Generated Index (PGI) is an individualized measure of quality of life (QOL) that allows patients to identify the areas of life that are important to them. Although the PGI has immense potential for use in clinical and research settings, its validity has not been assessed in PD. The purpose of this study is to estimate how well areas of QOL that patients with PD nominate on the PGI agree with ratings obtained from standard outcome measures. Methods. Patients with PD completed the PGI and various standard patient-reported outcome (PRO) measures. The PGI and standard PRO measures were compared at the total score, domain, and item levels. Pearson’s correlations and independent t-tests were used, as well as positive and negative predictive values. Results. The sample (n = 76) had a mean age of 69 (standard deviation 9) and were predominantly men (59%). The PGI was moderately correlated (r = −0.35) with the standardized disease-specific QOL measure Parkinson’s Disease Questionnaire (PDQ-8). Within one severity rating, agreement between the PGI and different standard outcome measures ranged from 85 to 100% for walking, 69 to 100% for fatigue, 38 to 75% for depression, and 20 to 80% for memory/concentration. Conclusion. This study demonstrates that nominated areas of QOL on the PGI provide comparable results to standard PRO measures, and provides evidence in support of the validity of this individualized measure in PD.